Effect of variations in terminal contact resistances on the current distribution in high-temperature superconducting cables. (21st January 2015) - Willering, G P; van der Laan, D C; Weijers, H W; Noyes, P D; Miller, G E; Viouchkov, Y
Abstract: Future application of high-temperature superconductors in large volume, high field magnets and in magnet current distribution systems requires cabling of RE-Ba2 Cu3 O7 − δ coated conductor tapes. The substantial aspect ratio of RE-Ba2 Cu3 O7 − δ coated conductors and the highly resistive buffer layers in these tapes make the development of compact and homogeneous cable terminals complex. The contact resistance between individual tapes and the cable terminations of two types of high-temperature superconducting cables was determined at 77 K at relatively low current ramp rates using a non-destructive method. The current distribution between tapes in the cables caused by a variation in contact resistance was calculated with a simple model, which was validated using different experimental methods. The results show that the current distribution at low current ramp rates in cables made from RE-Ba2 Cu3 O7 − δ coated conductors is mainly dictated by the variations in contact resistances between tapes in the cable and the cable terminals. Development of practical cable terminals that minimize the variations in contact resistances is therefore instrumental for the successful application of high-temperature superconducting cables in magnets.